2017
DOI: 10.1111/fcp.12329
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide upregulates gene expression of glucagon‐like peptide‐1 receptor and nerve growth factor in streptozotocin/nicotinamide‐induced diabetic mice

Abstract: Glucagon-like peptide-1 (GLP-1) is an incretin hormone that has modulating effects on insulin release. GLP-1 and receptors for GLP-1 are widely expressed throughout the body including the brain. The expression of GLP-1 receptors is very specific to large neurons in hippocampus, neocortex, and cerebellum. GLP-1 receptor stimulation enhances glucose-dependent insulin secretion and lowers blood glucose in type 2 diabetes mellitus. Studies on adipobiology of neurotrophins have focused on nerve growth factor (NGF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Although there are many available treatments for T2DM [3], there is still a very urgent need to develop new drugs for the treatment of this disease. Recently, the clarification of the molecular mechanisms underlying the development of metabolic syndrome and the identification of novel targets for the prevention and therapy of T2DM have been widely studied by worldwide researchers [4–6]. It has now been clarified that the serum level of transforming growth factor β (TGF‐ β ) increased in patients with T2DM [7,8], and the TGF‐ β /Smad pathway was involved in the emergence of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many available treatments for T2DM [3], there is still a very urgent need to develop new drugs for the treatment of this disease. Recently, the clarification of the molecular mechanisms underlying the development of metabolic syndrome and the identification of novel targets for the prevention and therapy of T2DM have been widely studied by worldwide researchers [4–6]. It has now been clarified that the serum level of transforming growth factor β (TGF‐ β ) increased in patients with T2DM [7,8], and the TGF‐ β /Smad pathway was involved in the emergence of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although this finding is preliminary and requires further investigation, it enhances knowledge regarding GLP-1 role in mental disorders. Animal studies have suggested that development of diabetes is associated with a reduction in the expression of GLP-1R in the hippocampus (Gumuslu et al, 2018). In addition, decreased hypothalamic expression of GLP-1R in individuals with type 2 diabetes has been previously documented (Ten Kulve et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…After acclimatization, diabetes was induced in balb/c mice with slight modification, as described earlier [ 67 ]. All overnight-fasted mice were given a single dose of (i.p) injection of STZ 150 mg/kg body weight (BW), dissolved in citrate buffer of 0.1 m after 15 min of nicotinamide at 240 mg/kg BW (i.p).…”
Section: Methodsmentioning
confidence: 99%